2023
DOI: 10.1038/s41562-023-01531-x
|View full text |Cite
|
Sign up to set email alerts
|

Early morning university classes are associated with impaired sleep and academic performance

Abstract: Attending classes and sleeping well are important for students’ academic success. Here, we tested whether early morning classes are associated with lower attendance, shorter sleep and poorer academic achievement by analysing university students’ digital traces. Wi-Fi connection logs in 23,391 students revealed that lecture attendance was about ten percentage points lower for classes at 08:00 compared with later start times. Diurnal patterns of Learning Management System logins in 39,458 students and actigraphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 62 publications
(71 reference statements)
3
10
0
Order By: Relevance
“…Immediately after the pandemic, our participants seemed to have taken advantage of the opportunity to sleep longer by pushing back their wake‐up time. Educators and especially policymakers should take note of this and potentially reduce those early morning classes and responsibilities that overlap with students' needed sleeping hours and are associated with impairments to health and academic performance (see Yeo et al., 2023). Not only would this be a well‐received policy change, it would also help students to remember the information they learn better and improve their physical health (Walker, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Immediately after the pandemic, our participants seemed to have taken advantage of the opportunity to sleep longer by pushing back their wake‐up time. Educators and especially policymakers should take note of this and potentially reduce those early morning classes and responsibilities that overlap with students' needed sleeping hours and are associated with impairments to health and academic performance (see Yeo et al., 2023). Not only would this be a well‐received policy change, it would also help students to remember the information they learn better and improve their physical health (Walker, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…1 Sleepiness in this particular population can be explained by a considerable deterioration in sleep hygiene with entry to higher education, such as a decrease in sleeping hours or irregular sleep patterns due to early classes, university social lifestyle, and academic demands. [8][9][10][11]15 To this can be added other psychosocial stressors that increase the risk of anxiety, depression, and insomnia that usually occur with drowsiness. 1,[5][6][7] It is necessary to keep in mind that sleepiness can be a symptom of mental disorders such as anxiety and depression, which are highly frequent in university students in the global context.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] On the other hand, sleepiness in adolescent and young adult students, in most cases, is due to poor sleep hygiene secondary to behavioral changes to meet schedules and other academic demands. [8][9][10][11]15 In medical students, two systematic reviews showed a high prevalence of sleepiness by applying the Epworth scale for sleepiness. Jahrami et al 16 included nine studies that included 2,587 participants and found a pooled prevalence of sleepiness of 34.6% (95% CI 18.3-50.9).…”
Section: (Which Was Not Certified By Peer Review) Preprintmentioning
confidence: 99%
See 1 more Smart Citation
“…Moving elementary school times earlier does not impact outcomes, which is important because of the busing demands of moving middle and high school start times later 45 . Older adolescents and young adults are also affected by the earlier start times of their college classes, with shorter sleep duration and lower grades 46 . A separate study showed that college students who got less sleep had lower grades 47 …”
Section: Later School Start Timesmentioning
confidence: 99%